Manuscripts and Archives Comparative Views on Record-Keeping - Bausi, Alessandro; Brockmann, Christian; Friedrich, Michael; Kienitz, Sabine (Studies in Manuscript Cultures, 2018)
The archive is traditionally considered the counterpart of the library, the one storing records, the other housing "books." There is evidence, however, that this institutional division of labor reflects certain historical and social constellations. The present volume addresses the question of this complex interrelationship with case-studies from an impressive variety of ancient, traditional, and living cultures.